2021
DOI: 10.24251/hicss.2021.020
|View full text |Cite
|
Sign up to set email alerts
|

Human Decision Making in AI Augmented Systems: Evidence from the Initial Coin Offering Market

Abstract: The growing consensus that human intelligence and artificial intelligence are complementary has led to Human-AI hybrid systems. As digital platforms incorporating human-AI hybrids, platform designers need to evaluate the influence of AI on human judgment, and how such hybrid systems perform. In this paper, we investigate: Are human decisions influenced by AI agents in high uncertainty environments, such as evaluating ICO projects? Under what situations are humans able to mitigate AI agents-induced errors? Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Basu et al 39 2021 This study suggests that humans deploy AI agents as filters and pay greater attention to the riskier suggestions because they have an asymmetric framing impact on the recommendations.…”
Section: Paper Year Key Findings Limitations and Open Issuesmentioning
confidence: 87%
See 2 more Smart Citations
“…Basu et al 39 2021 This study suggests that humans deploy AI agents as filters and pay greater attention to the riskier suggestions because they have an asymmetric framing impact on the recommendations.…”
Section: Paper Year Key Findings Limitations and Open Issuesmentioning
confidence: 87%
“…However, the coin's founders diverted the funds and unlawfully financed certain real estate assets without indicating any income source. Basu, Saunak, et al 39 suggested that human specialists can use AI agents as a filter that rates poorly and spend more time researching projects. Karimov et al 38 investigated how effectively one can anticipate if an offering is a fraud.…”
Section: Fake Initial Coin Offerings (Ico)mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, new cryptocurrency brings surveillance value to the detection of fraud via public authentication and also public value that is reflected by people's acceptance (Alstyne, 2014). Related studies examined the effects of digital currencies on monetary systems (Iwamura et al, 2014), their extreme volatility and negative bubbles (Bianchetti et al, 2018;Fry & Cheah, 2016), surveillance applications (Foley et al, 2019), design of token contracts (Malinova & Park, 2018), blockchain adoption for solving counterfeiting (Pun et al, 2021), and the role of artificial intelligence-based ratings (Basu et al, 2019) in an initial coin offering (ICO). Notably, Liu et al (2021) showed the importance of the technological sophistication of ICO projects when it comes to valuing ICO success, implying that technological savviness is critical for cryptocurrency investments.…”
Section: Production and Operations Managementmentioning
confidence: 99%
“…In other words, the several definitions of ADM indicate that there are several shades of grey in the world of automated decision-making -from algorithms supporting and augmenting human agents' decisionmaking to humans fully delegating the task to algorithms [11], [15], [30], [31]. This is in line with Rai et al's view that as digital technologies continue to penetrate our work and daily lives, we are observing the design and deployment of a variety of human-AI hybrids that range in human-AI interdependence from substitution (AI replaces humans) to augmentation (humans and AI augment one and another) and assemblage (AI and humans are dynamically brought together to function as an integrated unit) [32].…”
Section: Automated Decision-making (Adm)mentioning
confidence: 99%